Ursolic acid prevents angiotensin II-induced abdominal aortic aneurysm in apolipoprotein E-knockout mice. (April 2018) - Zhai, Maocai; Guo, Junyi; Ma, Haiyan; Shi, Wei; Jou, David; Yan, Dan; Liu, Tianshu; Tao, Jingwen; Duan, Jialin; Wang, Yina; Li, Sheng; Lv, Jiagao; et al.
Abstract: Background and aims: Abdominal aortic aneurysms (AAA) is a chronic inflammatory disease in which signal transducer and activator of transcription 3 (STAT3), and disintegrin and metalloproteinase 17 (ADAM17) play important roles. However, it remains unclear whether ursolic acid (UA), a natural pentacyclic triterpenoid carboxylic acid, can have an impact on STAT3 and ADAM17 and hence influence the formation of AAA. The objective of this study was to characterize the potential effect of UA on the pathogenesis of AAA and on STAT3 and ADAM17. Methods: Male ApoE -/- mice were infused with angiotensin II (AngII) (1000 ng/kg/min) for 4 weeks to induce AAAs. Daily intragastric gavage with 100 mg/kg UA or tap water containing Tween 80 as controls was provided. Immunohistochemistry, cell viability assay, colony formation, wound healing assay, and Western blot were used to explore the potential effect of UA on AAA. Results: UA decreased the incidence of AngII-induced AAA in mice. UA alleviated the degradation of elastin fibers and inflammation and decreased the expression of MMP2, MMP9, ADAM17 and phospho-STAT3 (pSTAT3) in aorta of mice induced with AngII. UA inhibited the constitutive and stimuli-induced (AngII and tumor necrosis factor-α) expression of MMP2, MMP9, ADAM17 and pSTAT3 in vascular smooth muscle cells (VSMCs). Furthermore, UA decreased cell viability, and suppressed colony formation and wound healing in vitro . Conclusions: We demonstrated that UA ameliorated the severity of AAA and exhibited an inhibitory effect on the expression of pSTAT3 and ADAM17. UA might emerge as a promising agent contributing to the prevention or treatment of AAA. Highlights: Ursolic acid (UA) ameliorates the development and severity of abdominal aortic aneurysm. UA inhibits pSTAT3 and the expression of MMPs in VSMCs and abdominal aortic aneurysms (AAA) ApoE -/- mice. UA suppresses the expression of ADAM17 in VSMCs and AAA ApoE -/- mice.